Leadership, communication, and social influence : a theory of resonance, activation, and cultivation - Ruben, Brent D.; Gigliotti, Ralph A. (Emerald points., 2019)
Can you identify five political leaders whose ideas you don't share but for whom you still have respect? Or multiple media channels and news outlets you tend to disagree with but still listen to? In an age of heightened and polarized ideologies and viewpoints, it is becoming increasingly important to engage in critical self-reflection about the dynamics of social influence in our personal and professional lives, and the responsibility we each bear as agents of social influence in local and global groups, teams, organizations, and communities.Ruben and Gigliotti challenge readers to bring a more nuanced understanding of communication and social influence to the decisions they make as aspiring leaders and followers. Throughout the book, the authors explore vexing questions, such as how some leaders in the workplace, community, or national political scene succeed in amassing large amounts of dedicated followers, and yet seemingly fail to exhibit the characteristics and competencies described by most experts in leadership? Or why certain social influence efforts seem to connect immediately and quite automatically with some audiences, while possibilities for influence with other constituencies may only develop over a longer periodor not at all? By exploring the convergence of leadership and communication, Ruben and Gigliotti evaluate the ways in which the perspectives, messages, and behaviors of a sender/leader and receiver/follower can resonate and the impact of this resonance on the responses and reactions of people around them.Designed for leadership and communication students, scholars, and practitioners, Leadership, Communication, and Social Influence: A Theory of Resonance, Activation, and Cultivation offers a timely exploration into the evolution of leadership, communication, and social influence, and sheds light on how we can all become more responsible leaders, followers, and citizens.